Specificity And Sensitivity for Malaria Detection by Rapid (Parahit) Detection Test and Microscopic Method - Taviad, Pankaj P; Javdekar, T B; Selot, Bhavna A; Chaudhari, Vipul P (National Journal of Community Medicine, 2011)
Malaria continues to be a major killer of mankind, especially in developing countries.1 It is a disease of antiquity, has proved to be a formidable deterrent to the cultural and socio-economic progress of man in tropical, subtropical and monsoon prone zones of world.2 One of the most pronounced problems in controlling the morbidity and mortality caused by malaria is limited access to effective diagnosis and treatment in areas where malaria is endemic.3 100 cases were analyzed in respect of clinical presentation by routine microscopic methods and the immune assay techniques namely pLDH antigen detection for rapid P. falciparum and P. vivax detection. More than two third (67%) positivity rate for P. falciparum blood smear. The pLDH antigen detection was positive in 58% of P. falciparum cases while 22% of P. vivax cases. Also, pLDH antigen detection immunoassay gives 100% specificity and 85.42% sensitivity.